Role in Disease Progression: Non-Motor Manifestations in Parkinson’s Disease (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Smell impairments occur several years before movement disorders. The results of observation of 213 patients with PD are presented. The presence of hyposmia in patients with early onset of PD is an important biomarker of the risk of future development of PD.